TAFSIR DAN HADITS TEMATIK TENTANG KESEHATAN - Fadliyanur Fadliyanur (STAI AL FALAH Banjarbaru, 2018)
Maintaining the health of yourself is an obligation which must be run by the entire human race especially special to Muslims. Because of these attitudes, including against myself. Islam teaches us to always keep good physical health and spiritually for the purpose of the study of religion and worship to God Almighty as the lack of life in the hereafter. Many verses of the Qur'an and Hadith that explain about keeping the health of yourself which will be discussed in writing below. Keywords: Tafsir, Hadith, health.